2023
DOI: 10.3390/ijms24108538
|View full text |Cite
|
Sign up to set email alerts
|

Can Pharmacogenetic Variants in TPMT, MTHFR and SLCO1B1 Genes Be Used as Potential Markers of Outcome Prediction in Systemic Sclerosis Patients?

Marina Jelovac,
Nikola Kotur,
Bojan Ristivojevic
et al.

Abstract: Systemic sclerosis (SSc) is a rare connective tissue disorder with highest morbidity and mortality among rheumatologic diseases. Disease progression is highly heterogeneous between patients, implying a strong need for individualization of therapy. Four pharmacogenetic variants, namely TPMT rs1800460, TPMT rs1142345, MTHFR rs1801133 and SLCO1B1 rs4149056 were tested for association with severe disease outcomes in 102 patients with SSc from Serbia treated either with immunosuppressants azathioprine (AZA) and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Plasmatic IL-35, compared to other published biomarkers, is easy to obtain via non-invasive techniques, as are its dynamics, and it can be associated with severity and classification regardless of the received treatment. However, it would be interesting to evaluate whether plasmatic IL-35 can be associated with other recent predictor markers, such as nailfold videocapillaroscopy or pharmacogenetic variant genes [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmatic IL-35, compared to other published biomarkers, is easy to obtain via non-invasive techniques, as are its dynamics, and it can be associated with severity and classification regardless of the received treatment. However, it would be interesting to evaluate whether plasmatic IL-35 can be associated with other recent predictor markers, such as nailfold videocapillaroscopy or pharmacogenetic variant genes [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with RA who are heterozygous for the TPMT3A allele have an increased risk of azathioprine-related haematopoietic and gastrointestinal toxicity compared to those with the wild-type allele [89,90]. A recent study investigated whether genetic variants in genes encoding enzymes involved in the methotrexate and azathioprine metabolic pathways, such as TPMT, MTHFR and SLCO1B1, are associated with disease severity in SSc patients receiving immunosuppressive drugs [76]. The authors confirmed the hypothesis that carriers of the alternative TPMT*3A allele have reduced TPMT enzyme activity, resulting in toxic metabolites and consequent AEs when azathioprine is administered.…”
Section: Safetymentioning
confidence: 99%